Dehydroaromatization with V2O5 - Karki, Megha; Araujo, Hugo C.; Magolan, Jakob (Synlett, 2013)
Vanadium pentoxide is evaluated as a dehydroaromatization reagent. Tetrahydrocarbazole is readily aromatized by V2O5 in refluxing acetic acid under both stoichiometric and catalytic conditions. Indoline, tetrahydroquinoline, and tetrahydroquinoxaline are effectively aromatized by V2O5/silica in refluxing toluene.
Keywords: oxidation; arenes; heterocycles; vanadium pentoxide; carbazoles